INTERNALISASI PESAN DAKWAH KULTURAL PADA MASYARAKAT MELAYU SAMBAS - Bob Andrian (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2020)
The problem of da'wah lately is a problem that cannot be avoided by preachers. This problem certainly has an impact on the future of Muslims, so that the preachers are also required to be wise in conveying da'wah messages. Judging from the history of da'wah, the development of Islamic preaching in several parts of the world, almost all of the Islam brought by preachers has always adjusted to the context of the preaching being occupied. This is because the settings for each period of mad'u have their own characteristics. Now, of course, the method isn't exactly the same as in the past. Da'wah problems that occur today are also more complex. For this reason, a critical study of the transformation of da'wah is needed in anticipating the problems faced by preachers. Therefore, Muslim scholars, preachers and da'wah experts are required to be able to reformulate effective da'wah methods. In this context, research on da'wah through culture is quite interesting as an effective solution to achieve the goals of da'wah. This field research, which was conducted using an ethnographic approach, describes the results that the interpretation of the message of da'wah through the traditions of zikir nazam and maulid has indicators of the effectiveness of da'wah both in terms of quantity and quality on the object of preaching.